Half a century of evolution in the management and conservation of community forests in northwestern Mexico - Heredia-Telles, Aide; Pérez-Verdín, Gustavo; Serrano-Flores, Maria Elena; Avila-Meléndez, Luis Arturo; Durán, Elvira; Cruz-Garcia, Francisco (Instituto de Ecología, A.C., 2021)
The theory of collective action applied to forest communities in Mexico has been a great alternative to study forest landscape conservation and the socioeconomic impacts generated in common pool resources. We analyzed the historical role of three forest ejidos in the State of Durango, including their organization and capacity building to deal with forest cover changes. Two periods ranging from the beginning of forest concessions to current community forest management (1960-2018) were compared. Semi-structured interviews were used to estimate two indexes that associate the internal organization of the communities: Social Organization Index and Community Institutionality Index. The cartographic series of the National Institute of Statistics and Geography were also used to determine the changes in forest cover within the analyzed period. Based on Ostrom’s principles of collective action, the effectiveness of the ejidos in conserving their resources was analyzed. Results show that the indexes have increased over time, suggesting that ejidos have improved their organization processes. In addition, there is a direct relationship between the forest land increase and both indices. The so-called community forest management model is a feasible strategy that can contribute to the preservation of these ecosystems. The internal organization of the communities, including their institutional arrangements, is a key factor to search for the sustainable management of these common-pool resources.